Understanding childhood constipation through the prism of the caretaker - Aureen Ruby DCunha; Sandeep B Rai; Swathi Sunil Rao; Neevan D'Souza (Wolters Kluwer Medknow Publications, 2023)
Aims: Childhood constipation is presenting with increasing frequency at pediatric surgical clinics. The caregiver's role in prevention and management is pivotal. This study aimed at determining mothers' knowledge, attitudes, and practices with regard to childhood constipation and the association of these with demographic variables. Materials and Methods: This was a survey-based descriptive study conducted at a tertiary care hospital in South India. Randomly selected mothers of children aged 1-10 years consulting for any problem other than constipation were included in the study. Data collection was done by means of a pretested and prevalidated questionnaire. Results: There were 169 mothers with a median age of 30 years. Over half were homemakers and of a rural background. Urban mothers scored better than their rural counterparts in the attitude section (P = 0.034). Mothers with greater knowledge had better attitude (P = 0.001) and practice (P = 0.020) scores. Those with higher attitude scores also fared better in the practice section (P = 0.04). Conclusions: Knowledge, attitude and practice concerning childhood constipation are connected to each other. South Indian mothers are sufficiently aware of the nuances surrounding childhood constipation, but focused large-scale outreach programs and health education are necessary to bridge the gaps.